O estudo de história a partir da construção de uma prancha de surfe com o pendão do agave, tendo o trabalho como princípio educativo - Alberoni, Lucas de Avelar (2018)
This thesis will indicate the results obtained in a research project accomplished at the Polytechnic Institute from Rio de Janeiro’s Federal University in Cabo Frio (IPUFRJ), from 2014 to 2016, regarding History education, in the project “Agave Surfboard”, for the High School Junior class alongside the Maritime Culture technical course. The IPUFRJ presents a proposal for integrated vocational training alongside High School, with counter-hegemonic basis and having polytechnic education as a reference and Project Pedagogy as an approach to education through labor. The Polytechnic Institute was active in the city of Cabo Frio from 2008 until 2016 and adopted a teaching methodology that aims for higher student autonomy by education through labor. The methodology implemented aligns polytechnic and project pedagogy, developing an interdisciplinary and full-time assignment. Hence, the “Agave surfboard” project consists in the construction of surfboards utilizing wood from the agave stalks (Furcrarea gigantea) as raw material. This plant has its origin in Mexico and its abundantly found in the Brazilian ecosystem, being an eco-friendly alternative material for polyurethane, which is a petroleum derivative compound and highly poluent. Therefore, this research seeks to make further reflections about the importance of History teaching, besides pointing out a few possibilities and presenting a proposal for History education, through more effective teaching methodologies, based in polytechnic, having labor as an educational principle, aspiring to overcome the reproduction of knowledge and the so called traditional educational system in Brazil.